Application of GMP and SSOP to the Production of Natural CO Frozen Red Kakap (Lutjanus sp.) Fillets at PT. Alam Jaya Surabaya - Pola S.T. Panjaitan; Iman Mukhaimin; Dita Dwi Ambarwati; Rahmad Surya Hadi Saputra; Liliek Soeprijadi (Universitas Islam Lamongan, 2025)
According to BKIPM-KKP data, throughout 2022 - 2023 there were a total of 29 cases or 0.028% of the total 102,570. The cause was the finding of heavy metal content such as mercury that exceeded the threshold, namely 2 cases in Germany and 2 cases in France. In addition, 1 rejection case in Spain related to the lack of temperature control, and 1 case in Russia related to the finding of E. coli bacteria. One of the considerations for consumers in choosing products to be consumed is to ensure that the food produced is safe for health with guaranteed hygiene. The implementation of good production methods and sanitation procedures is based on a standard guideline, namely Good Manufacturing Practices (GMP) and Standard Sanitation Operating Procedure (SSOP). This study aims to determine the GMP and SSOP of frozen red snapper fillets. The methods used were observation, interview, and active participation. The results of the cold chain implementation are in accordance with the standard, the results of the yield calculation are in accordance with the company standard of 43-44%, the results of GMP and SSOP analysis have met the standards of PERMEN KP Number 17 of 2019. Key words: GMP; SSOP; Fillet; CO